Psychopathological Risk Factors Associated with Body Image, Body Dissatisfaction and Weight-Loss Dieting in School-Age Adolescents - Antonio S. Cabaco; José D. Urchaga; Raquel M. Guevara; José E. Moral-García (MDPI AG, 2021)
Determining the comorbidity patterns leading to suffering behavioural eating disorders (BED) that are identifiable in the early stages of life, can help prevent their becoming chronic, as well as preventing the consequences deriving from the cost and effectiveness of intervention programs. The paper focuses mainly on analysing the association between behavioural/emotional risk factors and body image, body satisfaction and diet in school children, as well as confirming whether there are differences based on sex. Several questionnaires (Strengths and Difficulties Questionnaire and several items of Health Behaviour in School-age Children) including these variables were distributed and completed by the 647 adolescents (16 year olds on average) who took part in the research project. The findings confirmed a differentiated risk profile in adolescent girls in that they had greater prevalence of emotional symptoms as a general psychopathological trait, although this was offset with their prosocial behaviour. Additionally, the findings also allowed us to conclude that the factors that predict vulnerability to BEDs are sex, the presence of emotional symptoms and social and behavioural issues. At the end of this paper, we discuss some implications and consequences that should be taken into account for future work.